Review of The emperor's new drugs: Exploding the antidepressant myth - Spiegel, Sharon B. (American Journal of Clinical Hypnosis, 2011)
Reviews the book, The Emperor's New Drugs: Exploding the Antidepressant Myth by I. Kirsch (see record [rid]2010-01164-000[/rid]). The author describes the fascinating journey that began with his research interest on the placebo effect and depression and evolved into his role as an investigative journalist, documenting the pharmaceutical industry’s role in misinforming the public about the limited effectiveness of the selective serotonin reuptake inhibitors (SSRI) antidepressants. The book is appropriate for all audiences, well written, easy to understand and accessible to the general public. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Antidepressant Drugs; Major Depression; Pharmaceutical Industry; Placebo; Serotonin Reuptake Inhibitors; antidepressant drugs; major depression; pharmaceutical industry; placebo; selective serotonin reuptake inhibitors